An Overview of Global Wheat Market Fundamentals in an Era of Climate Concerns. (2nd July 2017) - Enghiad, Aliakbar; Ufer, Danielle; Countryman, Amanda M.; Thilmany, Dawn D.
Abstract : Wheat is a key global commodity in terms of acreage and tradeable value and as a staple in household diets. Many factors affect wheat prices including climate, yields, oil prices, lagged prices, and imports. In addition to gradually and consistently increasing global wheat demand, these market drivers are posited to impact world prices and, ultimately, food security. To investigate how these factors differentially influence wheat markets, an extensive survey of literature regarding wheat market fundamentals was conducted, as well as a trend analysis using a uniquely compiled data set specific to significant wheat-producing areas. Previous studies show that imports, climate, oil prices, and past prices, among other factors, have a significant relationship with changes in the world wheat price. This study compiles and compares these same key variables from five major wheat export countries/regions for the time frame from 1980 to 2013.